2014
DOI: 10.1016/j.immuni.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease as a Model for Translating the Microbiome

Abstract: The inflammatory bowel diseases (IBD) are among the most closely studied chronic inflammatory disorders that involve environmental, host genetic, and commensal microbial factors. This combination of features has made IBD both an appropriate and a high-priority platform for translatable research in host-microbiome interactions. Decades of epidemiology have identified environmental risk factors, although most mechanisms of action remain unexplained. The genetic architecture of IBD has been carefully dissected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
201
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(211 citation statements)
references
References 124 publications
(148 reference statements)
5
201
0
5
Order By: Relevance
“…In contrast, Enterobacteriaceae, another family of proinflammatory microbes found to have increased relative abundance in CD patients in both our cohort and the RISK study, did not correlate with Paneth cell phenotype, suggesting that the presence of inflammation may play a more important role than Paneth cell phenotype for Enterobacteriaceae colonization in CD. Together, our study and other previous reports suggest multiple mechanisms for how proinflammatory microbes become associated with CD patients (35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, Enterobacteriaceae, another family of proinflammatory microbes found to have increased relative abundance in CD patients in both our cohort and the RISK study, did not correlate with Paneth cell phenotype, suggesting that the presence of inflammation may play a more important role than Paneth cell phenotype for Enterobacteriaceae colonization in CD. Together, our study and other previous reports suggest multiple mechanisms for how proinflammatory microbes become associated with CD patients (35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionsupporting
confidence: 82%
“…Given that the T300A polymorphism causes increased cleavage by caspase 3 and downregulation of ATG16L1 expression in human and mouse cells (Murthy et al, 2014), we think that among our mutants, Atg16 d67 is the best to model the disease in flies. Alterations in gut flora are also detected in all Atg16 mutant flies, similar to the perturbed commensal microbiota in IBDs (Huttenhower et al, 2014;Sartor, 2008).…”
Section: Discussionmentioning
confidence: 59%
“…IBD is a complex disease influenced by both environmental and genetic factors. Genome-wide association studies (GWAS) have identified over 100 distinct loci that confer risk of or protection against developing IBD (Anderson et al, 2011;Franke et al, 2010;Huttenhower et al, 2014;Liu et al, 2015). Mechanistic studies on these associated genes have revealed complex interplay between intestinal microbiota and mucosal immunity.…”
Section: Ibd Overviewmentioning
confidence: 99%